An Enclave of Affordability Past? Resident Perceptions of Development and Housing on Madison’s North Side - Major, Michael; Krueger, Marshall; Villegas, Diego (My University, 2019)
In the summer of 2019, the City of Madison classified the majority of neighborhoods in North Madison as susceptible to gentrification and its population as vulnerable to displacement. In this report, we document residents' and local leaders' perceptions of these classifications and how they imagine their community's future as their neighborhoods face increased development pressure. By documenting resident perceptions, the commercial and housing landscape, archival documents, and observations of public meetings, we provide an analysis on development pressure facing this enclave of affordability. We conclude that the city’s classification is contested by residents, that there is no consensus among homeowners that gentrification is occurring, and that various stakeholders are promoting conflicting goals for the future of North Madison.
Includes Maps, Photographs, Tables, Appendices and Bibliography.
Keywords: Gentrification; Displacement; Affordable Housing; Madison; Development